Economic integration, labor reallocation, and growth - Pascal Hetze (Universität Rostock, Institut für Volkswirtschaftslehre, 2006)
This paper develops an endogenous growth model with continuous labor reallocation. Economic integration increases the home availability of technologies globally developed. The wider technology pool has implications for the vintage structure of the manufacturing sector and affects the revenues earned in the two sectors R&D and manufacturing. The free exchange of technologies across the borders leads to structural change and labor reallocation within manufacturing and between the sectors. If there arises too much job destruction caused by economic integration, unemployment may be a consequence of more openness to technologies developed abroad.
Keywords: F43; O33; J63; 330; economic integration; job destruction; job creation; endogenous growth